In search of general patterns of manufacturing development - Haraguchi, Nobuya (UNIDO ViennaAT, 2010)
Reviews past work on the subject with a focus on the 1989 Syrquin and Chenery study which was the most comprehensive and complete work of their industrial development pattern studies. Proposes an alternative model for estimating the development patterns of sub-sectors within the manufacturing industry. Illustrates the patterns of sub-sectoral developments for ten different country groups based on their demographic and geographic conditions. Suggests some policy implications. Presents conclusions.